Comparative analysis of crisp and fuzzy multi- criteria decision making methods for supplier selection in an automotive manufacturing industry - Ahmad, Nazihah; Mat Kasim, Maznah; KRS, Shanmugam (ExcelingTech Publishers, 2019)
Selecting a supplier is a crucial task in today’s competitive business environment. A systematic, trusted and supportive method of evaluating supplier is necessary to select the right supplier that meets customers’ expectation in ensuring an efficient continuous supply chain. Multi-Criteria Decision Making (MCDM) methods are able to handle this complex problem when there are many suppliers with multiple conflict criteria. Thus, the aim of this paper is to conduct a comparative analysis of the use of crisp and fuzzy MCDM methods for supplier selection in an automotive manufacturing industry. Four methods; AHP-AHP, AHP-VIKOR, FAHP-FAHP, FAHP-VIKOR are used to calculate the relative importance of five criteria and sixteen sub-criteria and ranking eighteen suppliers. Results show that different methods provide a quite similar ranking of suppliers.